Penerapan Teknik Guided Note Taking dalam Meningkatkan Kemampuan Membaca Teks Drama - Andriani Andriani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2017)
The purpose of research study to describe about influence of the guided note taking technique to skill of reading drama text. Outcomes through the application of guided note taking technique of student class VIIIB SMP Negeri 2 Mamasa. The research is classroom action research. Procedur of the research is (1) planning, (2) action, (3) observation, and (4) reflection. The instruments used is a test of reading drama text and observation of student activity. In the first cycle the results showed that the average of skill of reading drama text is 70,08, and second cycle the average of skill of reading drama text is 75,00. Which means that the application of guided note taking can improve reading drama text skill of students.